PENDIDIKAN VOKASIONAL TEKNIK MESIN PADA ERA GLOBAL DI SMK NEGERI 1 ADIWERNA - Ramdhan, Tanto (JPP, 2011)
The focus of this research is the management of vocational education techniques describedin the problem of engine research: planning, implementation and evaluation ofvocational education of Mechanical Engineering. The method used is a qualitative approachwith case studies of type procedures: (1) pre-field, (2) ekprolasi focus, then (3)data analysis. Techniques to obtain data by: (1) interviews, (2) observation, and (3) studythe document. Data analysis with inductive thinking techniques with the procedure: (1)data reduction, (2) data display, then (3) draw conclusions and verification. Results of research:(1) Planning is carried out through: the identification of needs through to the informationsearch and internet industry, the formulation of plans through workshops bypresenting representatives from business and industry, establishing a plan with the boardattended the plenary meeting of teachers, parents, learners and the school committee, andevaluation plan by Evabang, (2) exercising their education by organizing, coordinationand cooperation with business and industry to implement the learning in the form of thetheory by inserting character education, industry practices and work practices, and (3)Evaluation, including: evaluation external of the BAN-S/M and ISO, an internal evaluationconsists of: the performance evaluation of teachers by the school principal, teacherevaluation of learning by training the eye, prakerin evaluation by the industry, competencytest by the department manager, Middle Semester Deuteronomy, Deuteronomy End ofSemester, Examination Theory and practice with the committees, and labor recruitmenttest by the manager of BKK and industry recruiters.Keywords: vocational education, engineering mechanical